A New Instrument for Intrahepatic Access of Glissonian Pedicles During Anatomical Liver Resections. (August 2014) - Makdissi, Fabio F.; Machado, Marcel Autran C.; Surjan, Rodrigo C.
The knowledge of liver anatomy has led to a rapid evolution based on the intrahepatic distribution of the portal pedicle. One great advance in liver surgery was the used of segment-based liver resections. Techniques based with intrahepatic Glissonian access of portal pedicles were described to safely perform anatomical liver resections. We have earlier described a standardized intrahepatic access to right and left liver segments' pedicles without hilar dissection for anatomical hepatectomies. To improve the intrahepatic Glissonian technique, we designed a new atraumatic instrument for liver pedicle retrieval based on the anatomical liver landmarks. This new instrument was successfully employed in seventeen consecutive liver resections with minimum blood loss and without any complications related to its use. This new instrument, atraumatic retriever, replaces the right angle dissector or Gray clamp. The new instrument can slide easily and smoothly around Glissonian pedicle with a simple movement. This new instrument is a useful adjunct for performing intrahepatic access for liver resections. It can also be used to compass delicate anatomical structures such as esophagus and major abdominal vessels. The retriever can further be used in other common situations, including access for Pringle maneuver, encircling proximal esophagus during total gastrectomies or esophagectomies, and access for total vascular exclusion of the liver. This instrument can also be adapted to be used for laparoscopic liver resections.